Ethanol as a renewable biofuel: Combustion characteristics and application in engines - Mendiburu, Andrés Z.; Lauermann, Carlos H.; Hayashi, Thamy C.; Mariños, Diego J. [UNESP]; Rodrigues da Costa, Roberto Berlini; Coronado, Christian J.R.; Roberts, Justo J.; de Carvalho, João A. [UNESP] (Elsevier, 2022)
The present review article aims to study different aspects involving ethanol combustion and utilization. The review deals with the production and sustainability of corn-based and sugarcane-based ethanol as a starting point to present ethanol as a renewable and sustainable biofuel. The second step is to present the current understanding of ethanol combustion, regarding the application of thermodynamic theory and detailed chemical kinetic mechanisms to model the combustion processes. The utilization of ethanol implies consideration of safety parameters related to its combustion. Therefore, a section was dedicated to discussing the flammability limits and detonability limits of ethanol and their experimental determination. The application of gasoline-ethanol blends in spark ignition engines and diesel-ethanol blends in compression ignition engines is also addressed. New techniques (as dual injection) are being considered to improve the combustion efficiency. Also, the use of biodiesel in diesel-ethanol-biodiesel blends has shown to be a promising possibility. The greenhouse gas emissions obtained in different experimental works with internal combustion engines running on different fuel blends involving ethanol were also reviewed. Ethanol potentially increases the thermal efficiency of internal combustion engines and reduces the NOx emissions. Finally, the possibility of integrating internal combustion engines and ethanol fuel cells is also considered.
Keywords: Chemical kinetics; Combustion; Ethanol; Internal combustion engines; Sustainability